Pengaruh Customer Trust dan Perceived Risk terhadap Purchase Decision pada Produk Skintific dengan Customer Satisfaction sebagai Variabel Mediasi - Tsania Lisfayla Shofa; Nurul Komariyatin (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the influence of customer trust and perceived risk on purchase decision for Skintific products, with customer satisfaction serving as a mediating variable. The research employs a quantitative approach, utilizing purposive sampling to collect data from 160 respondents who are active users of Skintific skincare products. Primary data were gathered through structured online questionnaires, and the analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that both customer trust and perceived risk exert a significant direct influence on purchase decision. Specifically, higher levels of trust positively drive consumers' buying choices, while lower perceived risk also significantly encourages purchase intentions. Regarding the mediator, perceived risk has a significant negative effect on customer satisfaction, indicating that greater uncertainty or potential drawbacks reduce overall satisfaction with the product. In contrast, customer trust demonstrates a positive relationship with customer satisfaction, although this effect is not statistically significant. Furthermore, the results of the indirect effect analysis show that customer satisfaction does not significantly mediate the relationships between customer trust and perceived risk on purchase decision. This suggests that the impact of trust and risk perceptions on buying behavior operates predominantly through direct pathways rather than being channeled through satisfaction levels. This condition may occur because skincare purchase decisions tend to be driven more strongly by perceived product efficacy, safety assurance, and visible results rather than by emotional satisfaction alone. Consumers are likely to base their decisions on tangible evidence of effectiveness and risk reduction prior to purchase, making satisfaction which is typically formed after product usage less influential as an intervening variable.